1982
DOI: 10.1002/jobm.19820220210
|View full text |Cite
|
Sign up to set email alerts
|

Microbial methane oxidation in the River Saar

Abstract: I n the River Saar, the distribution of methane-oxidizing bacteria and their metabolic activity were determined in vertical and longitudinal profiles. At the sediment surface about two orders of magnitude more methane oxidizers were detected than in the overlying water. In the river as well as in laboratory experiments, the rate of methane oxidation was closely related t o the concentration of methane. Most of the methane produced by methanogenic bacteria in the sediment escaped into the atmosphere. On the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…). This result is consistent with the detection of such methanotrophs in other freshwater ecosystems (Zaiss et al ; Sundh et al ; Oswald et al ; Samad and Bertilsson ) and previous incubation studies with these microorganisms that indicated growth at cold temperatures (Sundh et al ; Ricão Canelhas et al ). Moreover, these lineages were detected in higher proportions on the large‐pore–size filters than on the small‐pore–size filters (up to 14.89% and 11.84% on the large‐pore–size filters for Crenothrix and Methylobacter, respectively, vs. up to 1.04% and 3.94% on the small‐pore–size filters).…”
Section: Resultssupporting
confidence: 92%
“…). This result is consistent with the detection of such methanotrophs in other freshwater ecosystems (Zaiss et al ; Sundh et al ; Oswald et al ; Samad and Bertilsson ) and previous incubation studies with these microorganisms that indicated growth at cold temperatures (Sundh et al ; Ricão Canelhas et al ). Moreover, these lineages were detected in higher proportions on the large‐pore–size filters than on the small‐pore–size filters (up to 14.89% and 11.84% on the large‐pore–size filters for Crenothrix and Methylobacter, respectively, vs. up to 1.04% and 3.94% on the small‐pore–size filters).…”
Section: Resultssupporting
confidence: 92%
“…MOB constitute the main microbial processors of CH 4 at oxic/anoxic interfaces in stream sediments (Trimmer et al, 2010(Trimmer et al, , 2015Buriánková et al, 2012;Shelley et al, 2014Shelley et al, , 2015 where MOB can account for up to 30% of prokaryotic cell numbers (Buriánková et al, 2012). CH 4 oxidation (MOX) can be an important ecosystem process, equivalent to up to 46% of net photosynthetic production in chalk streams (Trimmer et al, 2010;Shelley et al, 2014) and reducing CH 4 evasion fluxes by 70% (Zaiss et al, 1981;de Angelis and Scranton, 1993). Among MOB, low-affinity CH 4 oxidizers with substrate affinity constants K S [i.e., the substrate concentration for which the MOX rate is half the maximum reaction velocity (V max )] in the micromolar range are adapted to elevated CH 4 concentrations typical for hot spots of methanogenesis.…”
Section: Introductionmentioning
confidence: 99%